Agricultural inputs policy under macroeconomic uncertainty: Applying the kaleidoscope model to Ghana’s Fertilizer Subsidy Programme (2008–2015) - Resnick, Danielle; Mather, David (Michigan State University, 2016)
Ghana’s Fertilizer Subsidy Programme (GFSP) was initiated in 2008 in response to the global food and fuel price crisis. Although initially intended to be a temporary measure that became increasingly expensive as Ghana’s macroeconomy deteriorated, farmers, civil society organizations, and politicians began to expect the subsidy on an annual basis. This paper applies the kaleidoscope model for agricultur and food security policy change to the case of GFSP. In doing so, it uses a variety of analytical tools to highlight how many of the weak outcomes of GFSP can be attributed to the nature of the broader policy process that has surrounded GFSP as well as the underlying political and institutional context in which policy making occurs in Ghana. Based on semi-structured interviews conducted with knowledgeable stakeholders spanning the government, donor, civil society, and research communities, the paper identifies the bottlenecks that need to be addressed if the program is to be more effective in the future.